Dearth of school library collection: inhibition to reading promotion programme in Nigerian schools (2012)
This study investigated the dearth of collection and reading promotion programmes in school library media centres (SLMC) in Nigerian schools. The survey research design method was adopted for the study while questionnaire was used as the major instrument of data collection. One hundred and thirty seven (137) copies of questionnaire were administered on school librarians/school library media specialists/teacher-librarians, heads of library, and proprietors/proprietress of schools that were among the participants that attended the 25th and 26th Annual Conferences of the Nigerian School Library Association at Abeokuta, 2010 and Ado Ekiti, 2011 respectively. However, only ninety two (92) copies of the questionnaire were found to have useful responses that were used for the study. The findings of the study revealed a dearth of learning resources such as periodical literature and audiovisual resources to be used in promoting and developing favourable reading culture among pupils in Nigerian schools. Also, the study revealed a dearth of reading promotion programmes such as story hour and book talks in SLMC in Nigerian schools. The study highlights the need for the provision of adequate funding for schools and SLMCs in Nigeria to enable schools stock their SLMCs with adequate and relevant collection and also to enable them carry out programmes that will help in developing the reading culture of Nigerian children.